The First 24 h Hemodynamic Management in NICU after Revascularization Surgery in Moyamoya Disease - Jie Song; Yu Lei; Long Chen; Chao Gao; Wei Ni; Xing Wu; Gang Wu; Ying Mao; Jin Hu; Yuxiang Gu (Behavioural Neurology)
Objective. To evaluate whether hemodynamic factors are risk factors for prognosis in moyamoya disease (MMD). Materials and Methods. The retrospective study reviewed a single-center MMD cohort in Huashan Hospital from August 2017 to January 2020. Stroke events in 30 days and follow-up modified Rankin Scale (mRS) grade were recorded. Systematic assessments with perioperative mean arterial pressure (MAP), red blood cell (RBC) parameters, and fluid management were also conducted. Logistic regressions were applied to evaluate the predictors of worse outcomes. Data was analyzed using SPSS 24.0. Results. Admission to neurological intensive care unit (NICU) totalled about 347 after revascularization surgery. The result showed that the higher the postoperative MAP level (favorable group 95.7±11.4 mmHg vs. unfavorable group 103.6±10.4 mmHg, p<0.001) and the greater the MAP variability (favorable group 0.26±13.2 vs. unfavorable group 7.2±13.5, p=0.006) were, the higher the patient’s follow-up mRS grade was. What is more, a higher early postoperative Hb level also seemed to predict a worse long-term clinical outcome (favorable group 116.9±17.1 g/L vs. unfavorable group 123.7±13.0 g/L, p=0.03), but the difference disappeared after adjusting sex and age. Logistic regression analyses showed that a higher level of postoperative MAP (β=0.024, 95% CI (0.004, 0.044), and p=0.02) within the first 24 h in NICU might be the short-term risk factor. For long-term outcome, a higher level (β=1.058, 95% CI (1.022, 1.096), and p=0.001) and a greater variability (β=30.982, 95% CI (2.112, 454.414), and p=0.01) of postoperative MAP might be the negative predictors of mRS grade. Conclusions. The early postoperative hemodynamic management might be extremely critical for patients with MMD. Both high postoperative MAP levels and large MAP variability might affect the prognosis. What is more, we also found that a higher postoperative Hb level might be related with a worse outcome.